ON THE STARK BROADENING OF Ru III SPECTRAL LINES - Dimitrijević, Milan S. (Bulletin of Natural Sciences Research, 2021)
Stark broadening parameters, full widths at half maximum (FWHM) and shifts for spectral lines within six multiplets of doubly charged ruthenium ions have been calculated, for an electron density of 1017 cm-3 and temperature range from 10 000 K to 160 000 K. Calculations have been performed with the simplified modified semiempirical (SMSE) approach. In the case of two multiplets, it is possible to apply the full modified semiempirical method. The corresponding calculations have been performed and results are compared in order to test and determine the accuracy of the SMSE approach. The results are also used for the consideration of Stark width and shift regularities in Ru III spectrum.